Meeting in the Middle: Towards Successful Multidisciplinary Bioimage Analysis Collaboration - Schlaeppi, Anjalie; Adams, Wilson; Haase, Robert; Huisken, Jan; MacDonald, Ryan B.; Eliceiri, Kevin W.; Kugler, Elisabeth C. (Frontiers in Bioinformatics, 2022)
With an increase in subject knowledge expertise required to solve specific biological questions, experts from different fields need to collaborate to address increasingly complex issues. To successfully collaborate, each individual involved in the collaboration must take steps to “meet in the middle”. We thus present a guide on truly cross-disciplinary work using bioimage analysis as a showcase, where it is required that the expertise of biologists, microscopists, data analysts, clinicians, engineers, and physicists meet. We discuss considerations and best practices from the perspective of both users and technology developers, while offering suggestions for working together productively. Although this guide uses bioimage analysis as an example, the guiding principles of these perspectives are widely applicable to other cross-disciplinary work.